Harmony of Acculturation in the Land of Panji Sakti: Weaving the Traces of Nyama Bali and Nyama Selam in Tegallinggah’s Cross-Cultural Relations - Suadnyana, Kadek Nova; Rahayuni, Luh Sulistya; Aditya, Ida Bagus Gede (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study aims to explore forms of cultural acculturation between Hindu (Nyama Bali) and Muslim (Nyama Selam) communities in Tegallinggah Village, Sukasada District, Buleleng Regency, Bali. The research employed a descriptive-historical qualitative approach through literature study, documentation of village archives, and narrative analysis. The findings reveal three main points. First, the arrival of Islam in Tegallinggah began in the 17th century when Bugis groups came to support Panji Sakti’s expedition and later settled in the area. Second, Subak Wingin serves as a functional example of acculturation in natural resource management by combining the Tri Hita Karana principles with Muslim social practices, fostering interfaith solidarity in irrigation governance. Third, Muslim marriage traditions in Tegallinggah integrate local Balinese vocabulary, symbols, and practices, such as the use of Malay pantun during courtship, the base tampin ritual during engagement, and the mepacar and metangas ceremonies. These practices reflect values of tolerance and respect for local customs passed down through generations. The study underscores that cultural acculturation in Tegallinggah is not merely passive tolerance but an active, everyday practice that shapes a unique hybrid cultural identity. The results are expected to contribute to the development of local history learning materials that promote pluralism and social harmony among students.